2021
DOI: 10.3389/fcell.2021.625719
|View full text |Cite
|
Sign up to set email alerts
|

The Arp2/3 Inhibitory Protein Arpin Is Required for Intestinal Epithelial Barrier Integrity

Abstract: The intestinal epithelial barrier (IEB) depends on stable interepithelial protein complexes such as tight junctions (TJ), adherens junctions (AJ), and the actin cytoskeleton. During inflammation, the IEB is compromised due to TJ protein internalization and actin remodeling. An important actin regulator is the actin-related protein 2/3 (Arp2/3) complex, which induces actin branching. Activation of Arp2/3 by nucleation-promoting factors is required for the formation of epithelial monolayers, but little is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 71 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…Gag reaches a site where actin branching is lower and the assembly is easier at this location, or this could be induced by Gag recruiting a debranching factor to favor the assembly nucleation at that membrane location. Since CK666 is a debranched actin drug targeting directly the Arp2/3 complex, we hypothesis that Gag could hijack the Arp2/3 inhibitor Arpin to promote HIV-1 Gag assembly locally at the cell membrane as Arpin has been studied for the similarity of its function with the effect of CK666 (57, 58). Indeed, we found that Arpin membrane localization increased upon HIV-1 Gag expression in cells suggesting an interaction between Gag and Arpin that we revealed by an Arpin/Gag co-immunoprecipitation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Gag reaches a site where actin branching is lower and the assembly is easier at this location, or this could be induced by Gag recruiting a debranching factor to favor the assembly nucleation at that membrane location. Since CK666 is a debranched actin drug targeting directly the Arp2/3 complex, we hypothesis that Gag could hijack the Arp2/3 inhibitor Arpin to promote HIV-1 Gag assembly locally at the cell membrane as Arpin has been studied for the similarity of its function with the effect of CK666 (57, 58). Indeed, we found that Arpin membrane localization increased upon HIV-1 Gag expression in cells suggesting an interaction between Gag and Arpin that we revealed by an Arpin/Gag co-immunoprecipitation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ARPC5 and CLDN16 were significant genes related to the pathway, 'Tight junction', which may explain the characteristics of cluster 1. The intestinal epithelial barrier consists of interepithelial protein complexes, including tight junctions, adherens junctions, and the actin cytoskeleton [42]. ARPC5 protein is an important actin regulator responsible for actin cytoskeletal remodeling associated with compromised intestinal epithelium [42].…”
Section: Cluster Analysis Identifies 3 Distinct Phenotypes and Genoty...mentioning
confidence: 99%
“…3,4 As a crucial part of the intestinal mucosal barrier, the mechanical barrier is mainly composed of intestinal epithelial cells and tight junction (TJ) proteins between cells 5,6 whose damage will cause the pathogenic bacteria and endotoxin to migrate into extraintestinal tissues, activate the immune system, and aggravate the inflammatory response. 7,8 Gut microbiota is essential for protecting the gut from injury, 9,10 and generally a stable intestinal microbiota structure may prevent inflammation by resisting the colonization of pathogenic bacteria. 11 Besides, recent studies showed that gut microbiota-derived metabolites could dramatically affect the immune balance and maintain the intestinal mucosal integrity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, the global incidence of UC has been increasing yearly . Even though the precise etiology of UC is incompletely understood, the critical factor of the compromised gut barrier during UC pathogenesis has been highlighted by a large body of research. , As a crucial part of the intestinal mucosal barrier, the mechanical barrier is mainly composed of intestinal epithelial cells and tight junction (TJ) proteins between cells , whose damage will cause the pathogenic bacteria and endotoxin to migrate into extra-intestinal tissues, activate the immune system, and aggravate the inflammatory response. , …”
Section: Introductionmentioning
confidence: 99%